The Relationship between Social Support and Optimism in Overseas Students Who Are Working on Their Final Assignments - Potoboda, Angriani; Kristianingsih, Sri Aryanti (Journal of Social Research, 2023)
Overseas students are students who study far from their home area and certainly far from family and close friends, so sometimes they are required to be independent and must be able to adapt to their new environment. As final students who are working on their final project, one of the challenges encountered is their ability to overcome difficult times in the process of working on their thesis, one of which is the decline in the level of optimism, so that the role of the environment and the closest people is needed to increase optimism in students. This study aims to determine whether there is a relationship between social support and optimism in regional students who are working on their final project. The subjects of this study amounted to 110 people who were regional students from various universities in Central Java. In this study using incidental sampling method for sampling technique. The measuring tools used are the social support scale and the optimism scale. The social support scale measures three sources of social support, that came from family, friends, and supervisors. Based on the results of data analysis, the value of the correlation coefficient of family social support with optimism of 0.530 with sig was obtained. = 0.000 for the family social support variable, then for the social support aspect of friends, a Pearson correlation value of 0.584 with Sig was obtained. = 0.000, and for the third aspect of social support, namely the supervisor, a Pearson Correlation value of 0.612 was obtained with SIG. = 0.000, where p<0.05, which means that there is a positive relationship between the three aspects of social support and optimism in regional students who are working on their final project.